2014
DOI: 10.1016/j.ijcard.2013.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Initial experience with the balloon expandable Edwards-SAPIEN Transcatheter Heart Valve in Australia and New Zealand: The SOURCE ANZ registry: Outcomes at 30days and one year

Abstract: TAVI in the ANZ clinical environment has demonstrated excellent outcomes for both the TA and TF approaches in highly selected patients. These results are consistent with those demonstrated in European, Canadian registries and the pivotal US clinical trials. ACTRN12611001026910.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
2

Year Published

2014
2014
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 27 publications
2
15
2
Order By: Relevance
“…19 The current study represents one of the largest single centre experiences from Australia and New Zealand, comprising outcomes involving procedures with three different valve systems and four access approaches. Our results compare favourably with registry data published in Australian multicentre registries, 5,20 and other smaller series from single sites. 6 Our study is unique in that it describes a relatively large experience with both femoral percutaneous and surgical (trans-apical and trans-aortic) TAVI.…”
Section: Discussionsupporting
confidence: 86%
“…19 The current study represents one of the largest single centre experiences from Australia and New Zealand, comprising outcomes involving procedures with three different valve systems and four access approaches. Our results compare favourably with registry data published in Australian multicentre registries, 5,20 and other smaller series from single sites. 6 Our study is unique in that it describes a relatively large experience with both femoral percutaneous and surgical (trans-apical and trans-aortic) TAVI.…”
Section: Discussionsupporting
confidence: 86%
“…The use of the Edwards Sapien TAVI have been reported locally by the ANZ investigators [6] and replicated the results of PARTNER trial. In this issue, the Australian and NZ Corevalve Investigators [7] demonstrate that excellent mid-term outcomes of this alternative TAVI technology may be obtained by locally trained heart valve teams.…”
mentioning
confidence: 72%
“…Overall 14 studies (n = 2,772) reported stroke outcomes, of which 4 studies used the standardized VARC definition . The overall crude incidence of 30‐day stroke in the pooled cohort was 4.0%.…”
Section: Resultsmentioning
confidence: 99%